Feasibility and applicability of pulmonary nodule day surgery in thoracic surgery - Han, Jiajun; Zhu, Ruijun; Ding, Cheng; Zhao, Jun (Frontiers in Surgery, 2022)
Background: More patients with lung diseases were identified with low-dose computed tomography (CT) popularization and increasing physical examination awareness. Day surgery was routinely conducted in many departments as a relatively mature diagnosis and treatment mode. Thus, this study aimed to assess the feasibility of day surgery in thoracic surgery for pulmonary surgery and provide guidance for selecting suitable patients. Methods: This study retrospectively analyzed the clinical data of patients with pulmonary diseases in the single medical group of Thoracic Surgery at the First Affiliated Hospital of Soochow University, Jiangsu, China, from September 2021 to March 2022. Patients were divided into the day and routine surgery groups following chest tube removal within 48 h postoperatively and the discharge criteria. Each group was further divided into the wedge and anatomic lung resection groups. The feasibility of day surgery in thoracic surgery was evaluated by calculating the percentage of the day surgery group and comparing the clinical data of the two groups, and corresponding guidance was given for selecting suitable patients for day surgery. Results: The day surgery group accounted for 53.4% of the total number of patients in both groups. Data comparison revealed differences in age, hypertension, coronary heart disease, pulmonary function index, nodule localization, pleural adhesion, and total postoperative drainage in the wedge resection and age, gender, smoking history, pulmonary function indexes, intraoperative adhesions, operative duration, and total postoperative drainage volume in the anatomic lung resection. Results: This study concluded that more than half of the pulmonary surgery can be applied to the treatment mode of day surgery, and day surgery can be applied to the screened patients. It conforms to the concept of accelerated rehabilitation and can speed up bed turnover so that more patients can receive high-level medical treatment promptly.